In Vitro Activity of Isavuconazole against Aspergillus Species and Zygomycetes According to the Methodology of the European Committee on Antimicrobial Susceptibility Testing - Perkhofer, Susanne (American Society for Microbiology (ASM), 2009)
We evaluated the MICs of isavuconazole (ISAV) against 96 isolates of Aspergillus species and 36 zygomycetes according to the methodology of the European Committee on Antimicrobial Susceptibility Testing. In addition, the in vitro activity was obtained for hyphal inocula. ISAV exhibited good antifungal activity against the tested isolates with the exception of Aspergillus niger and Mucorales. The in vitro activity of ISAV was comparable to that of voriconazole aside from Mucorales.